2012
DOI: 10.1371/journal.pone.0052129
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity and Impairment in Women with Systemic Sclerosis Compared to Women from a General Population Sample

Abstract: ObjectiveReports of low sexual activity rates and high impairment rates among women with chronic diseases have not included comparisons to general population data. The objective of this study was to compare sexual activity and impairment rates of women with systemic sclerosis (SSc) to general population data and to identify domains of sexual function driving impairment in SSc.MethodsCanadian women with SSc were compared to women from a UK population sample. Sexual activity and, among sexually active women, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
1
20
0
3
Order By: Relevance
“…All had an established diagnosis of pSS according to the American-European Consensus group criteria 3 and all were sexually active (women were classified as sexually active/inactive based on the question: "During the past 4 weeks, have you engaged in sexual activities with your partner?") 4 .…”
Section: Methodsmentioning
confidence: 99%
“…All had an established diagnosis of pSS according to the American-European Consensus group criteria 3 and all were sexually active (women were classified as sexually active/inactive based on the question: "During the past 4 weeks, have you engaged in sexual activities with your partner?") 4 .…”
Section: Methodsmentioning
confidence: 99%
“…1,[38][39][40][41][42][43] Compared with women in the general population, women with SSc are significantly less likely to be sexually active, and sexually active women with SSc are significantly more likely to be sexually impaired. 39,40,42 Factors that are independently associated with being sexually active include younger age, fewer gastrointestinal symptoms, and less severe Raynaud phenomenon symptoms. 41 Among women who are sexually active, sexual impairment is associated with older age, as well as with more severe skin involvement and breathing problems.…”
Section: Sexual Functionmentioning
confidence: 99%
“…It means that only 115 of 730 (16%) patients engaged in sexual activities without impairment. It was also confirmed that SSc patients are significantly less likely to be sexually active and more likely to be sexually impaired than the general population of women [46]. Severe sexual dysfunction was also observed in married women with systemic sclerosis.…”
Section: The Use Of the Fsfi Questionnaire In Systemic Sclerosis Patimentioning
confidence: 58%